Pengaruh Kepribadian Narsisme Akuntan Terhadap Praktik Profesi Tidak Etis - Ernia Dwi Anjani; Hero Priono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of narcissism personality in an accountant on unethical professional practice. This research uses a quantitative method by distributing questionnaires online to accountants through personal chat or group chat. Data analysis used in this study used multiple linear regression analysis by passing several tests including: Classical Assumption Test and Hypothesis Test. The results showed that the narcissism personality level of accountants at IAI Muda East Java is 7.82, which is relatively low, and the level of unethical professional practice is 15.47, which is low. Keywords: narcissism, accountant, unethical professional practices